Some Sort of Help for the Poor: Blurred Perspectives on Asylum (2015)
This article explores the distinction between economic and forced migration by following three Guatemalan day labourers in northern California who 'discover' the possibility of asylum after coming to the US as undocumented migrants. Vaguely understood as 'some sort of help for Guatemalans,' asylum acquires a confusing assortment of meanings for these men as they hear about it from other migrants and local NGOs. They thus face two problems that hinder their application. The first is that their own rendering of their reasons for migration can look both 'forced' and 'voluntary.' The second is that beyond the validity of their claims, their life in the US is embedded in the marginalization of the cohort of undocumented migrants they join. Whatever the outcome, the men thus continue to follow the logics of fear and mistrust that characterize undocumented day labourers in the United States. © 2014 The Author. International Migration © 2014 IOM.